Ancient Readers and their Scriptures, Engaging the Hebrew Bible in Early Judaism and Christianity. - Garrick Allen; John Anthony Dunne (Editors) (Ancient Judaism and Early Christianity, 2019)
explores the various ways that ancient Jewish and Christian writers engaged with and interpreted the Hebrew Bible in antiquity, focusing on physical mechanics of rewriting and reuse, modes of allusion and quotation, texts and text forms, text collecting, and the development of interpretative traditions. Contributions examine the use of the Hebrew Bible and its early versions in a variety of ancient corpora, including the Septuagint, Dead Sea Scrolls, New Testament, and Rabbinic works, analysing the vast array of textual permutations that define ancient engagement with Jewish scripture. This volume argues that the processes of reading and cognition, influenced by the physical and intellectual contexts of interpretation, are central aspects of ancient biblical interpretation that are underappreciated in current scholarship.